The Influence of Zusanli and Nonmeridian Acupuncture Points on the Survival Rate and Intestinal Tissue Features after Fatal Hemorrhagic Shock in Rats. (30th January 2013) - Shi, Xian; Zhong, Yuxian; Yao, Jiarui; Hu, Sen; Wang, Lu; Litscher, Gerhard
Abstract : Sixty Sprague-Dawley rats were divided into 5 groups: (a) control group (HS); (b) Immediate rehydration group (IFR); (c) ST36 electroacupuncture (EA) delay rehydration group (EA/DFR): EA at ST36 immediately after blood loss with infusion 3 h later; (d) EA nonmeridian rehydration group (SEA/DFR): EA at nonacupuncture sites with rehydration similar to EA/DFR; (e) ST36 EA group (EA): EA at ST36 immediately after blood loss with no rehydration. Forty-five percent of the entire blood volume was taken out to make lethal hemorrhagic shock models. We recorded the survival rate, intestinal tissue DAO content, and microcirculation. The survival rate of the EA/DFR group and the IFR group was significantly higher than that of the other three groups (P < 0.05 ). Twelve hours after blood loss, intestinal tissue DAO content of the EA/DFR group and the IFR group was significantly higher than that of the SEA/DFR group, EA group, and HS group (P < 0.05 and P < 0.01 ). The mucosal blood flow of the EA/DFR group and the IFR group was significantly higher than the other groups (P < 0.05 each). We conclude that EA improves the blood pressure and raises the early survival rate of hemorrhagic shock rats, maintains the intestinal barrier function, and improves the degree of intestinal ischemia.